Numerical Investigation of Ohmic Heating in Channel Flow - Salih, E. A.; Spotar, S. Y. (Gezira Journal of Engineering and Applied Sciences, 2012)
Heat generation by direct electric conduction (ohmic heating) in a fully developed channel flow was studied to evaluate interaction between the hydrodynamic, electric and the thermal phenomena involved under the effect of natural convection. The equations governing the system were solved numerically by CFD finite volume code (FLUENT6.1 software package). The velocity profiles accelerate more near the wall than at the center that makes the temperature distribution uniform in the channel span. The numerical model is validated with an earlier experimental study [El Moctar et all . 1996] and yielded good agreement.